Optimizing ZIS Funds in Islamic Banks: A Case Study of the Islamic Rural Bank in Yogyakarta - Anda; Ayu, Navirta; Zahra; Dwi Harmoyo (Mutanaqishah: Journal of Islamic Banking, 2025)
Purpose – This study aims to examine the strategies for optimizing the management of zakat, infak, and sadaqah (ZIS) funds in Islamic Rural Banks (BPRS) in the Special Region of Yogyakarta. Methodology – Using a qualitative approach and case study method, this research explores the practices of ZIS fundraising, distribution mechanisms, and empowerment program innovations implemented by the selected BPRS. Findings – The study finds that optimizing ZIS fund management in BPRS relies on three key strategies: community-based distribution, digital fundraising innovation, and collaborative empowerment programs. The synergy between BPRS, zakat institutions, and local stakeholders enhances public trust, increases participation, and strengthens the role of BPRS in promoting inclusive economic development. Implications – These findings provide actionable insights for BPRS and other Islamic financial institutions to design and implement more optimal and sustainable ZIS management strategies. The study also highlights the potential for BPRS to contribute more significantly to inclusive economic development through improved ZIS governance. Originality – This research contributes to the limited literature on the role of Islamic Rural Banks in ZIS management. It offers a fresh perspective by examining the integration of technology and stakeholder collaboration in a localized Indonesian context, which has been relatively underexplored in prior studies.